Confirmatory Factor Analysis of Active Aging Scale for Thai People in a Nursing Home - Juthavantana, Jantana; Sakunpong, Nanchatsan; Prasertsin, Ujsara; Charupheng, Monthira (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
The current study aims to analyze the structural factors of Active Aging Scale for Thai People (AAS-Thai) in a nursing home and to verify the consistency between the measurement model of AAS-Thai in a nursing home and empirical data. 200 participants were purposively selected. The instrument used was AAS-Thai consisting of seven components. The internal validity was 0.95. Data analysis was done using LISREL 8.72. The results of first order CFA showed that all indices meet the fit indices criteria ( = 377.57, /df = 0.89, p-value = 0.95, CFI = 1.00, GFI = 0.94, AGFI = 0.91, RMR = 0.03, SRMR = 0.03 and RMSEA = 0.00), factor loading ranged from 0.66 to 0.94, p = .01. The results of second order CFA also showed that all indices meet the fit indices criteria ( = 379.38, /df = 0.89, p-value = 0.93, CFI = 1.00, GFI = 0.94, AGFI = 0.91, RMR = 0.03, SRMR = 0.03 and RMSEA = 0.00), factor loading ranged from 0.72 to 0.97, p = .01. The components with the factor loading ranging from highest to lowest included: being actively engaged with society, being self-reliant, growing spiritual wisdom, engaging in active learning, maintaining healthy lifestyle, building up financial security and strengthening family ties for being cared for in the late life. The empirical data revealed that AAS-Thai was apt to be used as a measurement of active aging of Thai elderly in a nursing home.